2011
DOI: 10.1038/jhh.2011.35
|View full text |Cite
|
Sign up to set email alerts
|

Does hypertensive disorder of pregnancy predict offspring blood pressure at 21 years? Evidence from a birth cohort study

Abstract: Although few studies found that the offspring of women who experienced preeclampsia have higher blood pressure (BP) at childhood and adolescence, no study has observed whether this association exists for adult offspring. To examine whether maternal hypertensive disorder of pregnancy (HDP) predicts adult offspring BP. We followed a sub-sample of 2608 mother-offspring pairs for 21 years from an original cohort of 7223 singleton infants whose mothers gave birth in Brisbane, Australia between 1981 and 1983. HDP wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 28 publications
3
33
0
1
Order By: Relevance
“…15 CBP in the Avon Longitudinal Study of Parents and Children was significantly higher in 17-year-old offspring of mothers with GH (120.5 ± 11.3/66.0 ± 7.2-mm Hg) or preeclampsia (120.2 ± 10.1/66.6 ± 7.0 mm Hg) compared with non-PIH (117.6 ± 10.4/64.5 ± 6.8 mm Hg) even when adjusting for potential confounding factors in multivariable linear regression analysis. 15 Inconsistent with earlier studies, 15,31 including the Avon Longitudinal Study of Parents and Children, there were no significant associations between maternal GH and HBP in children at 7 years old in the present study. These findings were confirmatory when the 1:2 matched-case analyses were performed.…”
Section: Discussionsupporting
confidence: 61%
“…15 CBP in the Avon Longitudinal Study of Parents and Children was significantly higher in 17-year-old offspring of mothers with GH (120.5 ± 11.3/66.0 ± 7.2-mm Hg) or preeclampsia (120.2 ± 10.1/66.6 ± 7.0 mm Hg) compared with non-PIH (117.6 ± 10.4/64.5 ± 6.8 mm Hg) even when adjusting for potential confounding factors in multivariable linear regression analysis. 15 Inconsistent with earlier studies, 15,31 including the Avon Longitudinal Study of Parents and Children, there were no significant associations between maternal GH and HBP in children at 7 years old in the present study. These findings were confirmatory when the 1:2 matched-case analyses were performed.…”
Section: Discussionsupporting
confidence: 61%
“…In 2,868 young adult offspring of women enrolled during pregnancy into the Western Australia Pregnancy Cohort Study, offspring of hypertensive pregnancies were 2.5 times (95% CI 1.32-4.56, p = 0.004) more likely to have global lifetime risk scores above the 75th centile. Preeclampsia or hypertension resulting in preterm birth was associated with a 3-fold (95% CI 1.3-7.0, p = 0.01) greater risk of being hypertensive by age 20 years, with no differences in BMI [52,53].…”
Section: Cardiovascular Disease In the Offspring Of Preeclamptic Womenmentioning
confidence: 93%
“…Offspring of women with preeclampsia had a higher systolic blood pressure by 2.04 mm Hg (95% CI 1.33-2.76) and a higher diastolic blood pressure by 1.10 mm Hg (95% CI 0.47-1.73) in analyses adjusted for maternal and offspring BMI, offspring dietary sodium intake, and other potential confounders [54]. The Helsinki Birth Cohort Study observed that the offspring of preeclamptic pregnancies had almost double the lifetime risk of stroke (HR 1.9, 95% CI 1.2-3.0; p = 0.01) [52,55].…”
Section: Cardiovascular Disease In the Offspring Of Preeclamptic Womenmentioning
confidence: 99%
“…Moreover, epidemiological studies show that offspring born to pregnant polycystic ovary syndrome or preeclamptic mothers, who have elevated testosterone (T) levels [10][11][12][13][14], are more likely to have increased BP during postnatal life [15][16][17][18]. We have recently shown that the increases in BP in prenatal T-exposed adults were more pronounced in males than in females [6].…”
Section: Introductionmentioning
confidence: 99%